2023
DOI: 10.1186/s13073-023-01173-8
|View full text |Cite|
|
Sign up to set email alerts
|

Rare predicted loss-of-function variants of type I IFN immunity genes are associated with life-threatening COVID-19

Abstract: Background We previously reported that impaired type I IFN activity, due to inborn errors of TLR3- and TLR7-dependent type I interferon (IFN) immunity or to autoantibodies against type I IFN, account for 15–20% of cases of life-threatening COVID-19 in unvaccinated patients. Therefore, the determinants of life-threatening COVID-19 remain to be identified in ~ 80% of cases. Methods We report here a genome-wide rare variant burden association analysis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…The genomewide association meta-analyses that consisted of 49,562 COVID-19 patients from 46 studies across 19 countries indicated that specific mutations of the tyrosine kinase 2 (TYK2) gene could enhance the risk of becoming critically ill with COVID-19, while individuals who carried a variant in the dipeptidyl peptidase 9 (DPP9) gene were at elevated risk of developing critical disease (191,192). Lossof-function mutations in type I IFN (IFN-I) immunity genes (TLR3 and TLR7) might be connected with severe forms of COVID-19 in European populations (193)(194)(195). NLRP3 inflammasome gene variants were correlated with critical COVID-19 in the Brazilian population (196).…”
Section: Inflammasome Activation and Other Pathologiesmentioning
confidence: 99%
“…The genomewide association meta-analyses that consisted of 49,562 COVID-19 patients from 46 studies across 19 countries indicated that specific mutations of the tyrosine kinase 2 (TYK2) gene could enhance the risk of becoming critically ill with COVID-19, while individuals who carried a variant in the dipeptidyl peptidase 9 (DPP9) gene were at elevated risk of developing critical disease (191,192). Lossof-function mutations in type I IFN (IFN-I) immunity genes (TLR3 and TLR7) might be connected with severe forms of COVID-19 in European populations (193)(194)(195). NLRP3 inflammasome gene variants were correlated with critical COVID-19 in the Brazilian population (196).…”
Section: Inflammasome Activation and Other Pathologiesmentioning
confidence: 99%
“…As is noted by Bucciol, Moens, et al, STAT2 and related genes are under intense selective pressure, presumably driven by viruses. In recent years, it has also become increasingly appreciated that various impairments of type I IFN function, either from inborn errors or anti-IFN autoantibodies, have played an important role in morbidity and mortality from the SARS-CoV-2 pandemic ( 7 , 8 ). Thus, increasing evidence demonstrates that type I IFNs are a critical defense against the ubiquitous threat that viruses pose.…”
Section: Ifn Signaling and Resistance To Viral Infectionsmentioning
confidence: 99%
“…Human genetic variation associated with disease severity has revealed defective innate immune responses as another key determinant in COVID-19 disease outcomes. Patients with inborn errors in components of RNA-sensing and innate signaling pathways, including toll-like receptor 3 (TLR3), TLR7, interferon-regulatory factor 7 (IRF7), type-I IFN (IFN-I) receptors IFNAR1 and IFNAR2, tyrosine kinase 2 (TYK2) and oligoadenylate synthetase 1 (OAS1) are at high risk of developing critical and severe COVID-19 disease 24,15,1719,12,2022 . The crucial importance of innate-derived IFNs is further underscored by the discovery that up to 15 – 20% of critically ill patients with COVID-19 had preexisting auto-antibodies to IFN-I, which delayed viral clearance 2326 .…”
Section: Introductionmentioning
confidence: 99%